Modified impression technique for extreme mouth-opening limitation caused by systemic scleroderma - Paes-, Tarcisio Jose De Arruda [UNESP]; Nakano, Leonardo Jiro Nomura [UNESP]; Rossi, Natalia Rivoli [UNESP]; Rodrigues, Murilo Rocha [UNESP]; Watanabe, Helena [UNESP]; Inagati, Cristiane Mayumi [UNESP] (My University, 2021)
Systemic scleroderma is a relatively rare, autoimmune, chronic, and debilitating disease, and its etiology is unknown.The disease is characterized by vasomotor disturbances causing skin and mucosa hardening, hand stiffness, excess production of collagen fibers, and impairment of the internal organs associated with the immune system. Extreme mouth-opening limitation is one of the symptoms in the oral cavity, and compromises dental intervention. One of the fundamental steps when performing a dental procedure is dental arch impression. In the presented clinical case, limited mouth opening hindered the impression accuracy. The objective was to present an alterna-tive impression technique for a patient affected by scleroderma, with limited mouth opening and the need for oral rehabilitation with a removable partial prosthesis in the maxillary arch. An individualized tray was developed with design characteristics that allowed access to the oral cavity and removal, after which it was possible to perform the oral impression, reproducing the areas of interest without causing injury to the oral tissues.The orientation plan was elaborated after obtaining the cast. The teeth were assembled, tested in the mouth, and sent to the laboratory for acrylization. The prosthesis was placed once ready. The alternative impression technique enabled oral rehabilitation of the patient despite the mouth-opening limitation, and provided an accurate impression and a good prosthetic result. 1244389).
Keywords: Dental impression technique; Microstomia; Mouth rehabilitation; Removable partial denture; Systemic scleroderma